2020
DOI: 10.1002/pros.24018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and treating ROBO1−ve/DOCK1+ve prostate cancer: An aggressive cancer subtype prevalent in African American patients

Abstract: Background: There is a need to develop novel therapies which could be beneficial to prostate cancer (CaP) patients including those who are predisposed to poor outcome such as African-Americans. This study investigates the role of ROBO1-pathway in predicting outcome and race-based disparity in CaP patients. Methods and Results:Aided by RNA sequencing-based DECIPHER-testing and IHC analysis of tumors we show that ROBO1 is lost during the progressive stages of CaP, a prevalent feature in African-Americans. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Parray et al showed that ROBO1 negatively regulates motility and the invasiveness of primary prostate cancer cells, and its loss causes these cells to acquire invasive traits (21). Ferrari et al (22) reported that loss of ROBO1 causes disintegration of the DOCK1 complex that in turn triggers invasiveness of cancer cells through loss of E-Cadherin and activation of Rac1 signaling However, our results were different from those of Parray's. The present study showed that the knockdown of ROBO1 expression in prostate cancer cells resulted in a decreased capacity for migration and invasiveness.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Parray et al showed that ROBO1 negatively regulates motility and the invasiveness of primary prostate cancer cells, and its loss causes these cells to acquire invasive traits (21). Ferrari et al (22) reported that loss of ROBO1 causes disintegration of the DOCK1 complex that in turn triggers invasiveness of cancer cells through loss of E-Cadherin and activation of Rac1 signaling However, our results were different from those of Parray's. The present study showed that the knockdown of ROBO1 expression in prostate cancer cells resulted in a decreased capacity for migration and invasiveness.…”
Section: Discussioncontrasting
confidence: 91%
“…Current study suggested the clinical significance of ROBO1 expression based on the long-term oncological analysis. Comparing with the results of Ferrari et al (22), current analysis through the stratified stage and relatively large numbers of patients might be a distinction.…”
Section: Discussionmentioning
confidence: 42%
“…CPYPP, a DOCK (dedicator of cytokinesis) inhibitor known for its anti-cancer effects by disrupting the interaction between DOCK2 and Rac1 [ 24 26 ], as well as CsA and curcumin, induced significant cytoplasmic vacuolization (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%